2020
DOI: 10.3390/nu12113586
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Lacto-Ovo-Vegetarian Diet on the Plasma Lipidome and Its Association with Atherosclerotic Burden in Patients with Coronary Artery Disease—A Randomized, Open-Label, Cross-over Study

Abstract: A vegetarian diet has been associated with a lower risk of coronary artery disease (CAD). Plasma triacylglycerols, ceramides, and phosphatidylcholines may improve prediction of recurrent coronary events. We sought to investigate effects of a lacto-ovo-vegetarian diet (VD) on plasma lipidome in CAD patients and simultaneously assess associations of plasma lipids with the extent of coronary atherosclerotic burden. We analyzed 214 plasma lipids within glycerolipid, sphingolipid, and sterol lipid classes using lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Moreover, with respect to certain cancers, a strict vegan diet may be more beneficial than a lacto-ovo-vegetarian one, although further studies are needed (8,9). Intervention studies comparing vegan or vegetarian diets vs. omnivorous diets have shown beneficial effects of these diets on cardiometabolic risk factors (10), T2D (11), and obesity (12).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, with respect to certain cancers, a strict vegan diet may be more beneficial than a lacto-ovo-vegetarian one, although further studies are needed (8,9). Intervention studies comparing vegan or vegetarian diets vs. omnivorous diets have shown beneficial effects of these diets on cardiometabolic risk factors (10), T2D (11), and obesity (12).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, bioactive lipids have also been discovered as independent risk factors for CVD. Concentrations of specific ceramides in serum have been shown to predict major cardiovascular events [ 3 , 4 , 5 ], and ratios of ceramides to associate with CVD death, independent of other risk factors [ 6 , 7 , 8 ]. For example, CERT2, a new risk score based on specific phosphatidylcholines and ceramides in serum, is a significant predictor of CVD mortality, as shown in several independent cohorts [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that in the two active interventions, a higher ceramide score did not coincide with a high CVD risk, however, in the control arm, an elevated ceramide score was associated with a significantly higher CVD risk [ 188 ]. Finally, an additional RCT revealed that adherence to a VD reduced the ceramide concentrations, compared to the standard medical nutrition therapy for patients with coronary artery disease [ 182 ].…”
Section: Dietary Interventions As Anti-ceramide Treatmentsmentioning
confidence: 99%